Sensibility assessment of the HIV Disability Questionnaire. (April 2013) - O'Brien, Kelly K.; Bayoumi, Ahmed M.; Bereket, Tarik; Swinton, Marilyn; Alexander, Rob; King, Kenneth; Solomon, Patricia
<x xml:space="preserve">Abstract</x> Purpose: Our purpose was to assess the sensibility of the human immunodeficiency virus (HIV) Disability Questionnaire (HDQ), the first HIV-specific disability questionnaire. Methods: We administered the HDQ, a sensibility questionnaire and a structured qualitative interview to 22 adults living with HIV and five experienced clinicians. We considered the HDQ sensible if median scores on the sensibility questionnaire were ≥5 for adults living with HIV and ≥4 for clinicians for at least 80% of the items. We analyzed the interview data using directed qualitative content analytical techniques. Results: Questionnaire scores were ≥5 for 88% (15/17) of the items and ≥4 for 100% (17/17) of the items for adults living with HIV and clinicians, respectively. The interview analysis indicated participants felt the HDQ possessed face and content validity in all disability dimensions, had adequate response options, was easy to complete, and adequately captured the episodic nature of disability. Participants had mixed responses about the questionnaire title and provided recommendations to refine item wording and response options. Conclusions: The HDQ appears sensible for use with adults living with HIV. Next steps include further measurement property assessment. The HDQ may be used by rehabilitation clinicians and researchers to assess disability experienced by adults living with HIV.